Osallistumattomuus koululiikunnassa - Yläkoululaisten syyt jättää osallistumatta liikuntatunneilla - Mikkilä, Nelli; Vuoltee, Monika (2025)
This master’s thesis examines why students didn’t participate in lower secondary school physical education (PE) classes. The aim was to investigate the occurrence and reasons for non-participation, as well as students' opinions on school PE. The study also aimed to examine differences in non-participation between grade levels and genders. Non-participation refers to situations where a student purposefully does not engage in the teacher’s planned lesson activities. For example, a student may lean against the wall, lie down in the middle of an exercise or a game, leave the PE classroom without permission, or fool around. Non-participation is important research topic, as it occurs quite commonly in PE classes. Participation in PE lessons is important for students to achieve the goals of physical education.